Work-in-Progress--Game Design Informed by Learning Progressions for Science Practices - Metcalf, Shari J.; Sommi, Amanda; Haddadin, Sima; Scianna, Jennifer; Gagnon, David (2021 7th International Conference of the Immersive Learning Research Network (iLRN), 2021)
Learning progressions allow researchers to describe key milestones along a pathway of thinking about a topic or practice that ranges from beginner to advanced. For learning related to science practices, some progressions can be abstracted from specific content; others are connected to specific science understandings. This research centers on the design of a middle school science game to support learning of science practices through simulated immersive experiences in which students engage in science practices of experimentation, modeling, and argumentation. This work-in-progress paper describes the application of current research on learning progressions to the design of the game interface and interactions for Aqualab, a game to teach middle school science practices related to aquatic ecosystems.